Особливості мотивації створення екскурсійного продукту в сфері екологічного туризму - Демко, Валентина Сергіївна; Demko, Valentyna (Мелітополь, ТДАТУ, 2021)
UKR: В статті досліджено основні мотиватори та демотиватори екологічного туризму в Україні Визначено, що для стимулювання екологічного туризму потрібно об’єктивувати туристичний потенціал визначивши основні бізнес можливості території. Сформовано принципи та напрямки мотивації господарюван ня в сфері екологічного туризму. Запропоновано авторське бачення туристично-екскурсійних маршрутів для розвитку та популяризації території з використанням бізнес-потенціалу регіону.\\\\\\\\\ENG: Every year the number of people willing to rest in an ecologically clean area in the most natural condi tions increases. The article examines the main motivators and demotivators of ecological tourism in Ukraine. It is de termined that to stimulate ecological tourism it is necessary to objectify the tourist potential by identifying the main business opportunities of the territory. The principles and directions of motivation of management in the field of ecolog ical tourism are formed. The author's vision of tourist-excursion routes for development and popularization of the terri tory with use of business potential of the region is offered. Conclusions. Ecological tourist and excursion products have a high business potential for community development. Effective use of such potential should combine intellectual, educational, creative, natural-geographical, economic, financial, infrastructural, socio-cultural opportunities of a certain territory, combining ecological development of green tourism and economic activity in the field of ecological tourism. Due to the specifics of these areas of management and the complex socio-economic situation in Ukraine, it is necessary to stimulate the development of ecological develop ment in tourism. It should be carried out on the basis of territorial concentration and motivation of the population to manage in the field of ecological tourism with increasing powers of local authorities. Motivational approaches should be implemented by combining the basic principles of targeted support with balancing the need for deregulation, which will ensure transparent economic activity in the field of ecotourism and allow it to be institutionalized as an important factor in the welfare of the rural population in Ukraine.
Features of motivation for creation of excursion product in the field of ecological tourism
Keywords: туристичний продукт; екскурсійний маршрут; бізнес-потенціал; мотивація господарювання; екологічний туризм; tourist product; excursion route; business potential; motivation of management; ecological tourism